Modeling the Influence of Nitrogen Concentration on Optical Gain Performance in Gallium Nitride Arsenide/Gallium Arsenide Quantum Wells Vertical-cavity Surface-emitting Lasers - Shafiq, Amanj L.; Chaqmaqchee, Faten A.; Faraj, Mohammad Gh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
This study investigates the influence of nitrogen (N) concentration on the optical and gain characteristics of Gallium Arsenide (GaAs)/gallium arsenide (GaAs) quantum wells (QWs) based vertical-cavity surface-emitting lasers (VCSELs) using MATLAB simulations. Numerical simulations were performed how varying N content affects cavity design and optical confinement properties. The stopband behavior and resonant wavelength shift were analyzed through reflectivity spectra for different N concentrations. The results reveal a red shift in the resonance wavelength and redistribution of the electric field intensity within the cavity as the N concentration increases. Higher N concentrations reduce mirror losses. However, excessive N incorporation introduces scattering and interface imperfections, leading to increased internal losses. In addition, an increase in N percentage results in reduced optical confinement factor and material gain decrease, indicating a lower overlap between the optical field and the active area. Both the threshold density and transparency carrier density were observed to rise with N addition, implying a decrease in recombination performance. Reflection-mode spectra confirm a red shift and a reduction in gain peak with higher N content. This analysis focused on a critical design of GaNAs VCSEL structure, which makes a distinction between engineering index profiles for optimal gain overlap and adjusting the optical path length for spectral control. A N concentration in the range of 1–2% provides the optimal balance along gain enhancement, optical confinement, loss minimization, and reflection gain, which are (0.11, 0.099), (175 cm−1, 162 cm−1), and (20.26 dB, 19.66 dB), respectively, thereby providing the overall performance of GaNAs/GaAs QWsVCSELs.